The Perception and Estimation of Others' Pain according to Children - Grégoire, Mathieu (Pain Res Manag, 2016)
Accurate interpretation of pain expressed by others is important for socialization; however, the development of this skill in children is still poorly understood. Empathy for pain models propose two main components (affective and cognitive), which develop at different stages of life. The study's objective was to investigate the children's ability between 3 and 12 years of age to detect and assess the pain intensity in others using visual stimuli depicting either facial expressions of pain or hands in painful contexts. 40 preschool children and 62 school-aged children were recruited. Children observed series of stimuli and evaluated the pain intensity depicted. Results demonstrated that children as young as three years old were able to detect and assess pain in both types of stimuli and this ability continued to improve until the age of 12. Participants demonstrated better detection performance with hands than with faces. Results were coherent with the idea that the two types of stimuli presented recruit different processes. Pain detection in hands appears to rely mostly on affective sharing processes that are effective early in life, while older children's higher ability to perceive pain in facial expressions suggests that this ability is associated with the gradual development of cognitive processes.